2009
DOI: 10.1002/cncr.24608
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of pregnancy occurring before or after treatment of early breast cancer patients aged <35 years

Abstract: Two new linear and hyperbranched conjugated polymers P1 and P2 have been synthesized by Sonogashira coupling reaction, in which the main chain consists of bithiazole moieties as electron acceptors and triphenylamino groups as donors. The conjugated polymers were characterized by TGA, UV–vis absorption, fluorescence emission, electrochemical cyclic voltammetry, and two‐photon absorption measurements. They exhibited excellent solubility in organic solvents and high thermal stability (5% of weight loss at 299 °C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
6

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 64 publications
(48 reference statements)
4
31
0
6
Order By: Relevance
“…In a population-based analysis by Ives et al [13], subsequentpregnancywasevenassociatedwithsignificantly improved overall survival. Furthermore, a recent study by Largillier et al [14] analyzed 118 cases of pregnancy after breast cancer treatment and demonstrated that a pregnancy resultedina77%decreaseofdeath(p <0.001).Comparable resultswereobservedinotherstudies [15][16][17].…”
Section: Influence Of the Pregnancy On The Course Of Cancersupporting
confidence: 54%
“…In a population-based analysis by Ives et al [13], subsequentpregnancywasevenassociatedwithsignificantly improved overall survival. Furthermore, a recent study by Largillier et al [14] analyzed 118 cases of pregnancy after breast cancer treatment and demonstrated that a pregnancy resultedina77%decreaseofdeath(p <0.001).Comparable resultswereobservedinotherstudies [15][16][17].…”
Section: Influence Of the Pregnancy On The Course Of Cancersupporting
confidence: 54%
“…Becoming pregnant after a diagnosis of breast cancer does not appear to result in worse outcomes in case-control studies or cohort studies (4,5,7,8). In fact, in several series, pregnancy after a diagnosis of breast cancer appeared to result in a reduced risk of relapse (7)(8)(9), particularly for women who waited for 2 years after diagnosis to conceive (9).…”
Section: Will Pregnancy After a Breast Cancer Diagnosis Increase The mentioning
confidence: 98%
“…In fact, in several series, pregnancy after a diagnosis of breast cancer appeared to result in a reduced risk of relapse (7)(8)(9), particularly for women who waited for 2 years after diagnosis to conceive (9). A theoretical risk for women undergoing ovarian harvest before chemotherapy and later reimplantation (see below) is reintroduction of viable tumor cells micrometastatic to the ovary at diagnosis.…”
Section: Will Pregnancy After a Breast Cancer Diagnosis Increase The mentioning
confidence: 99%
“…Dans l'étude du groupe GETNA, réalisée chez 908 patientes âgées de moins de 35 ans traitées pour un cancer du sein entre 1990-1999, a été évalué le risque entraîné par la survenue d'une grossesse après traitement [105]. Treize pour cent des patientes ont mené à terme une grossesse spontanée après traitement du cancer du sein et aucun effet délétère sur la survie globale n'a été mis en évidence.…”
Section: Veille Bibliographiqueunclassified
“…Treize pour cent des patientes ont mené à terme une grossesse spontanée après traitement du cancer du sein et aucun effet délétère sur la survie globale n'a été mis en évidence. Avec un risque relatif de 0,23 et une valeur de p infé-p infé-p rieure à 0,001, la survie à cinq ans était de 97 % pour les patientes ayant une grossesse contre 80 % en l'absence de grossesse [105].…”
Section: Veille Bibliographiqueunclassified